RARE OBSERVATION OF PSEUDOTUMOR OF THE INTESTINE, COMPLICATED BY INTUSSUSCEPTION - V. F. Tskhai; I. Yu. Klinovitsky; L. Ye. Yerendeyeva; P. A. Moiseyev (Бюллетень сибирской медицины)
The aim is to report a rare observation of pseudotumors of small bowel leading to chronic invagination and recidivating small bowel obstruction.The case is interesting because the information about pseudotumors of small bowel is unavailable in the literature, whereas in large bowel they are quite frequently observed, and their number is a tendency to increase. A complication of pseudoturmors is a chronic invagination  of small bowel, which is also rarely observed (in 9.05–9.58%). Its clinical picture is subtle, causing difficulties in diagnosis. In the reported observation, the diagnosis “chronic invagination” was also made only at surgery, while the diagnosis “pseudoturmor” was made after histologic examination of the specimen.For well-timed diagnosis, in the presence of clinical findings of recidivating small bowel obstruction, chronic invagination should be considered as one of the possible causes of obstruction.